Biochar from pyrolysis of biological sludge from wastewater treatment - L. A. C. Tarelho; T. Hauschild; A. C. M. Vilas-Boas; D. F. R. Silva; M. A. A. Matos (Energy Reports, 2020)
It was studied the production of biochar by pyrolysis of biological sludge from wastewater treatment in the pulp and paper industry. The pyrolysis process was conducted in bench-scale fixed-bed reactor using distinct operating conditions of heating rate (2, 10, 20 and 30~C/min) and peak temperature (300, 375, 450, 525, and 600~C). The biochar yield is in the range 0.40 to 0.73 kg/kg dry sludge, and decreases with increasing peak temperature and heating rate. The organic matter content of the biochar is in the range 55.9 to 75.3%wt. (dry basis). Both the temperature increase and the heating rate increase promote the decrease of biochar volatile matter content within values between 14.4 and 48.4%wt. (dry basis). The biochar ash content increases with peak temperature and heating rate, and it has values in the range 24.7 to 44.1%wt. (dry basis). The corresponding fixed carbon content is between 26.2 and 42.4%wt. (dry basis), and increases with an increase in the peak temperature. The carbon concentration in the biochar is in the range 42.8 to 47.0%wt. (dry basis). The biochar pH is in the range 6.9 to 11.2, and the electrical conductivity (EC) is in the range 2.2 to 5.0 mS/cm.
Keywords: 330; Pyrolysis; Biochar; Biological sludge; Heating rate; Peak temperature